STUDI KORELASI PENDIDIKAN KARAKTER DALAM KELUARGA DAN RELIGIUSITAS PADA KOMUNITAS REMAJA HIJABERS - Suparno, Suparno (Faculty of Psychology, Diponegoro University, 2013)
Adolescence, individuals experience many changes , both physically , mentally , to changes in social adjustment . These changes cause problems that result in loss of mental balance . Character education in the family is needed by young people to be able to overcome these problems . Religion plays an important role in life . Teens need religion to satisfy the spiritual needs and find rest of his life . Teens who have a religion , is expected to have a good religiosity. The purpose of this study was to determine the relationship between educational character (character building) in the family of the religiosity in adolescents. The hypothesis proposed that there is a positive relationship between character education in families with adolescent religiosity. Measuring instruments used scales, namely religiosity scale and the scale of character education in the family. The results of the study were analyzed using simple regression analysis showed a significant positive correlation between religiosity variable character building . The relationship is indicated by a correlation coefficient of r xy = 0.527 and p = 0.000 ( p < 0.05 )